Creative tourism and residents: interactions in the context of artistic residencies in the Center region of Portugal - Inês Almeida; Carlos Cardoso Ferreira; Luís Silveira (Investigaciones Turísticas)
In approximately twenty years of research on creative tourism, the relevance of including residents in the creative tourism experience has been mentioned but not investigated in depth. This paper seeks to identify forms of resident integration in creative tourism contexts through a semi-systematic literature review and to determine how this inclusion is explored in local accommodation units with artist residencies in the Central region of Portugal. Following a qualitative case-study-based approach, semi-structured interviews were conducted with representatives of three accommodation units. The findings suggest four main formats of resident participation: (i) as experience providers, (ii) as consumers, and (iii) as responsible/consulted parties during the planning and development process(es) of the creative destination or product; and (iv) a more hybrid format in accommodation units with artist residencies, in which the resident is simultaneously a supplier and a consumer of the experience. The empirical results also suggest that this fourth integration format takes place mainly through specific programs for the local community and activities not limited to tourists. In the three cases, the dynamics with residents appear to generate several benefits in terms of economic growth, infrastructure and service development and, primarily, social sustainability. Also, the experience of tourists and artists in the residency is enhanced by contact with the local community. The findings of the study indicate that entities with attributes comparable to those under examination should utilize initiatives and partnerships promoted by their respective municipalities to reinforce collaboration between artist residencies and local communities.